PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL MIND MAPPING PADA SISWA KELAS IV SDS MUHAMMADIYAH IV JAKARTA - Putri Merdeka EB; Harri Naredi (Prosiding Seminar Nasional Berseri, 2020)
This study aims to improve the results of social studies learning by using Mind Mapping Models that were performed at SDS Muhammadiyah IV Jakarta. This research uses a classroom action research model (PTK) by Kemmis and McTaggart carried out on students of IVth class SDS Muhammadiyah IV Jakarta during the full semester of 2018/2019, has 22 students. Two cycles used, each of which consisted of three encounters. Studies have shown the results of social studies using the Mind Maping Models on each cycle have improved, on a first cycle with average score of 78 and second cycle experienced an increase in average value to 81, as a result of the student activity instrument observed by the collaborators in the first cycle of 64,30% and in the second cycle have improved to 82,10%, as a result of the teacher activity in the first cycle of 77,00% and the second cycle has improved to 85,70%.